2012
DOI: 10.2337/dc11-2375
|View full text |Cite
|
Sign up to set email alerts
|

Increased Toll-Like Receptor Activity in Patients With Metabolic Syndrome

Abstract: OBJECTIVEThe metabolic syndrome (MetS) is highly prevalent and confers an increased risk for diabetes and cardiovascular disease (CVD). While MetS is a proinflammatory state, there is a paucity of data on cellular inflammation in MetS. Toll-like receptors (TLRs) are classical pattern recognition receptors of the innate immune response.RESEARCH DESIGN AND METHODSThe aim of this study was to examine monocyte TLR2 and TLR4 in MetS patients without diabetes or CVD and control subjects since both of the receptors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 27 publications
(51 reference statements)
4
124
0
3
Order By: Relevance
“…suppressive, effect on TLR expressions in PBMCs (21) so that insulin deficit or insulin resistance would be expected to result in TLR expression upregulation. Indeed, TLR2 and TLR4 expressions have been shown to be increased in the skeletal muscle and adipose tissue of type 2 diabetic subjects (12,19), as well as in the monocytes obtained from the patients with both type 1 (36) and type 2 diabetes (14), and the metabolic syndrome (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suppressive, effect on TLR expressions in PBMCs (21) so that insulin deficit or insulin resistance would be expected to result in TLR expression upregulation. Indeed, TLR2 and TLR4 expressions have been shown to be increased in the skeletal muscle and adipose tissue of type 2 diabetic subjects (12,19), as well as in the monocytes obtained from the patients with both type 1 (36) and type 2 diabetes (14), and the metabolic syndrome (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to host defense against foreign pathogens, recent studies implicate a role of NF-kB (7,8,9,10,11) and TLR pathway (10,12,13,14,15,16,17,18,19,20) in the pathogenesis of obesity-and type 2 diabetesrelated insulin resistance and metabolic disturbances. Moreover, de Mello et al (10,11) demonstrated that in patients with the metabolic syndrome, the changes in insulin resistance were associated with the changes in the expression of genes involved in the NF-kB signaling pathways in peripheral blood mononuclear cells (PBMCs).…”
Section: Introductionmentioning
confidence: 99%
“…The natural ligand for TLR4 is lipopolysaccharide, the Gram-negative bacterial wall component that is structurally similar to FFAs [25]. Indeed, obese individuals show upregulation of TLR4 in cells and tissues (including monocytes), adipose tissue, and skeletal muscle [27,28]. Therefore, a diet high in saturated FFAs can activate TLR4, leading to JNK activation, which in turn activates nuclear factor (NF)-κB [25,29].…”
Section: Obesity Insulin Resistance and Lipotoxicitymentioning
confidence: 99%
“…Hence, in a preliminary analysis of the patients with the metabolic syndrome included in our study, in whom we had previously shown increased monocyte TLR4 activity that correlated with insulin resistance, NEFA and endotoxin levels [5], we assayed fetuin-A in remaining frozen plasma samples. All participants gave informed consent to participate in the original study and the protocol was approved by the UC Davis Institutional Review Board.…”
Section: Tlr4 Toll-like Receptormentioning
confidence: 99%